2020
DOI: 10.1155/2020/8824535
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Contamination of the Muscles of Three Fish Species from the Moulouya River (Lower Moulouya, Eastern Morocco)

Abstract: This study introduces a spatiotemporal evaluation of the metallic contamination with three trace metals (mercury, lead, and cadmium) in the muscles of three fish species (Lepomis macrochirus, Barbus callensis, and Barbus nasus), of which the samples were taken from three stations in the Moulouya River: the confluence of the Moulouya River and the Sebra River (station 1), the neighbourhood of the farms in the region of Aklim downstream from confluence of Lakhmis river (station 2), and the level of ancient bridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
3
7
0
1
Order By: Relevance
“…The lower concentration of Cd in muscle observed in this study suggests that muscle tissue is not an active site for the Cd accumulation process. In the scientific literature, similar values were recorded in the muscles of L. macrochirus , B. callensis , and B. nasus from the Moulouya River to Morocco [ 26 ], in the muscles of L. graellsii , R. rutilus , and L. gibbosus in the station 1 from the Llobergat River to Spain [ 27 ], and in C. carpio of Kasumigaura Lake in Japan [ 6 ]. While, low concentrations of Cd were found in the muscles of B. barbus , and L. cephalus from the Shahid Rajaei Dam in northern Iran [ 28 ], in the muscles of ten species caught at Šalek Lake in Slovenia [ 29 ], in fish B. barbatula , S. cephalus , and B. barbus from the Sûre River in Luxembourg [ 30 ], in three species from the Vaal Dam in South Africa [ 31 ], and in the muscles of T. nilotica from the High Dam Lake in Egypt [ 32 ].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The lower concentration of Cd in muscle observed in this study suggests that muscle tissue is not an active site for the Cd accumulation process. In the scientific literature, similar values were recorded in the muscles of L. macrochirus , B. callensis , and B. nasus from the Moulouya River to Morocco [ 26 ], in the muscles of L. graellsii , R. rutilus , and L. gibbosus in the station 1 from the Llobergat River to Spain [ 27 ], and in C. carpio of Kasumigaura Lake in Japan [ 6 ]. While, low concentrations of Cd were found in the muscles of B. barbus , and L. cephalus from the Shahid Rajaei Dam in northern Iran [ 28 ], in the muscles of ten species caught at Šalek Lake in Slovenia [ 29 ], in fish B. barbatula , S. cephalus , and B. barbus from the Sûre River in Luxembourg [ 30 ], in three species from the Vaal Dam in South Africa [ 31 ], and in the muscles of T. nilotica from the High Dam Lake in Egypt [ 32 ].…”
Section: Discussionsupporting
confidence: 57%
“…These levels detected in this study are all lower the European Community (regulation (EC) N° 1881/2006) for the Pb in fish flesh, which is in the order of 0.3 mg/kg of wet weight for muscle meat of fish [ 25 ]. The comparison with the data available in the literature indicated that similar concentrations of Pb were detected in the muscles of L. kimberleyensis from Vaal Dam to South Africa [ 36 ], in L. macrochirus , B. callensis , and B. nasus captured at the Moulouya River to Morocco [ 26 ], in the muscles of L. graellsii , R. rutilus , and L. gibbosus in the station 1 from the Llobergat River to Spain [ 27 ], and in G. holbrooki from Fouarat Lake and Sebou Estuary in Morocco [ 37 ]. However, low concentrations of Pb were found by Rashed et al [ 32 ], Wariaghli et al [ 38 ], Alam et al [ 6 ], Boscher et al [ 30 ], Plessl et al [ 31 ], and Petkovšek et al [ 29 ].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…A nivel general, los niveles de metales pesados encontrados en los músculos de la trucha arcoíris están por debajo de los niveles máximos permisibles (WHO/FAO, 2015; FSANZ, 2013; MHPRC, 2013; OMS, 2016; Memet et al, 2017; European Commission, 2008), lo cual es un aspecto favorable, puesto que aún no constituye problema para la salud pública, pudiéndose consumir sin mucha preocupación (Mahjoub et al, 2020). El comparativo entre ambas zonas evidencia algunas variaciones (p<0.05) en el contenido de los metales pesados, lo cual puede ser indicador de la diferencia en el contenido de estos contaminantes en los cuerpos de agua; Cuadro 2.…”
Section: Resultados Y Discusiónunclassified